Akad Mudharabah dalam Perspektif Fikih dan Perbankan Syariah - Chasanah Novambar Andiyansari (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
This study discusses how the implementation of the mudharabah contract in Islamic banking practices in general. As well as how the position of the mudharabah contract in fiqh and how the mudharabah contract scheme is. The purpose of this study was to determine the position of the mudharabah contract in fiqh and the practice of the mudharabah contract in Islamic banking in general. The research method used by the author in this study uses qualitative methods , while this type of research uses descriptive qualitative type, with data collection methods using the documentation method, where the researcher collects historical researches that aim to explore past data systematically and objectively. . The results of this study reveal that the Mudharabah contract is a collaboration between the fund owner or investor ( shaihb al-mal / rabb al-mal / investor) and the capital manager ( mudharib ) to do business on the basis of profit sharing ratios. Although the mudaraba contract has no basis in the Koran or implicit sunnah, this contract was used to carry out the trade by early generations of Muslims. The contract was developed by Fuqaha under the conditions in his name based on the general principles of sharia regarding justice.The practice of Islamic banking in implementing the mudharabah contract as financing in terms of partnership, the mudharabah contract is one of the banking products, namely in the form of time savings, for example hajj savings, sacrifices, and special deposits (special investment).